Pencegahan Stunting Pada Balita Desa Sukamenak Wilayah Kerja Puskesmas Wanaraja Kabupaten Garut - Nofita Setiorini Futri Purwanto; Siti Nurcahyani Ritonga; Ira Nufus Khaerani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Stunting is defined as a condition in which a child's height or length is below the standard height for their age. It is a chronic malnutrition problem caused by insufficient nutritional intake over an extended period of time. Stunting can result in disrupted productivity in adulthood and hinder a child's physical growth and cognitive development. In addition to nutritional factors, stunting is caused by socioeconomic, knowledge, and infectious disease factors. The objective of this activity is to provide counseling and dissemination about stunting, nutritional needs, and the preparation of unique and healthy food variations